2x+4=x-10

Simple and best practice solution for 2x+4=x-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+4=x-10 equation:


Simplifying
2x + 4 = x + -10

Reorder the terms:
4 + 2x = x + -10

Reorder the terms:
4 + 2x = -10 + x

Solving
4 + 2x = -10 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
4 + 2x + -1x = -10 + x + -1x

Combine like terms: 2x + -1x = 1x
4 + 1x = -10 + x + -1x

Combine like terms: x + -1x = 0
4 + 1x = -10 + 0
4 + 1x = -10

Add '-4' to each side of the equation.
4 + -4 + 1x = -10 + -4

Combine like terms: 4 + -4 = 0
0 + 1x = -10 + -4
1x = -10 + -4

Combine like terms: -10 + -4 = -14
1x = -14

Divide each side by '1'.
x = -14

Simplifying
x = -14

See similar equations:

| -16+2x=-24+13x | | X+9-4=17 | | 6x+2(1+2x)=4(-2+5) | | -0.4(-0.6)= | | 3w(w+2)=0 | | (x+2)(x+1)=10 | | -2(7m-8)-3=-5(1+4m)+8m | | 3x(2xy+3y-2x)= | | X-12=43 | | 5-5(6-5)= | | 6(1-4p)=-8(-4+4p)-2 | | 61-3x=13-9x | | -6x-3.2=-3x+4.4 | | -9(6+n)=-54 | | -4.3+(-9.3)= | | 3x^2y+5y=2x | | v=(3.14)(36)(16) | | 3(2x-1)-6(x-4)=-9 | | -8(1-2k)=8(k-3) | | 46+2=3(5x+1) | | (x^4)-(10x^3)+(21x^2)+40x-100=0 | | 5+16z-3=9z+93-6z | | 49-2x=9-7x | | 5a=2a+7 | | x=1.4-(1.2x) | | X+6.5=9.7 | | 5+3x=-2x | | -3+6v=3(3v+4) | | 4(5x+3)-5(2x+1)=27 | | 4x+9=40-3x | | 3(3x+1)=39 | | 6a=6a+7 |

Equations solver categories